2020
DOI: 10.1002/jum.15454
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lung Echo Texture in Pregnancies at Risk for Pulmonary Hypoplasia

Abstract: Pulmonary hypoplasia is associated with severe respiratory distress immediately after birth and frequently leads to neonatal death. In this study, we compared the fetal lung echo texture in pregnancies at high and low risk for pulmonary hypoplasia. Ultrasonic tissue heterogeneity was determined by a dynamic range calculation. This quantification uses a dithering technique based on the Floyd‐Steinberg algorithm, in which the pixels are transformed into a binary map. Pregnancies at high risk for pulmonary hypopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Fetal lung texture analysis has thus far only been explored using ultrasound images: Previous studies assessed lung maturity [ 31 ], identified cases at risk for pulmonary hypoplasia [ 32 ], and predicted neonatal respiratory insufficiency [ 33 ] with promising results. However, ultrasound studies used 2D fetal lung ROIs to extract texture features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal lung texture analysis has thus far only been explored using ultrasound images: Previous studies assessed lung maturity [ 31 ], identified cases at risk for pulmonary hypoplasia [ 32 ], and predicted neonatal respiratory insufficiency [ 33 ] with promising results. However, ultrasound studies used 2D fetal lung ROIs to extract texture features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Период роста наиболее уязвим для воздействия физических факторов, таких как уменьшение внутригрудного пространства. На период созревания, в свою очередь, влияют нарушения гормональной регуляции [16]. Сочетание этих факторов приводит к нарушению альвеоляризации.…”
Section: гипоплазия легкихunclassified
“…Гипоплазию легких можно диагностировать антенатально, постнатально, при морфологическом исследовании, ее можно заподозрить внутриутробно во время УЗИ при воронкообразной форме грудной клетки (отношение диаметра сердца к диаметру грудной клетки >0,5), выступающем животе, высоко располо-Таблица 3. Патологические состояния и заболевания, ассоциированные с легочной гипоплазией [4] Гистологическими признаками, подтверждающими гипоплазию легких, являются симплификация легочных долек и недостаточное число альвеол в ацинусе, нарушение дифференцировки альвеолярного эпителия, преобладание мезенхимы над площадью воздушных пространств, дистопия сосудов микроциркуляторного русла без формирования альвеолярнокапиллярных мембран [15][16][17]. Радиальный альвеолярный счет считается методом, позволяющим документировать лобулярную симплификацию, и выполняется подсчетом числа альвеол, пересекающих линию, соединяющую центр респираторной бронхиолы и ближайшую внутридольковую перегородку или плевру.…”
Section: гипоплазия легкихunclassified
“…The two most frequently used color mapping choices made by our sonographers are Ice and Sepia. We have used ultrasound texture analysis by composing a heterogeneity index (HI) to differentiate preterm from term fetal lungs and to evaluate pregnancies at risk for lung hypoplasia using grayscale ultrasound images 2,3 . We wanted to know whether a fetal lung HI obtained using Ice or Sepia images can be substituted for a fetal lung HI using grayscale images.…”
Section: Introductionmentioning
confidence: 99%